Atypical presentation of progressive young onset dementia - Elhusein, Bushra (BMJ Case Rep, 2018)
We present the case of a 34-year-old Jordanian woman who was referred to mainstream mental health services because of irritability, agitation, loss of appetite, withdrawal from family activities and sleeping difficulties. She was initially diagnosed with major depressive disorder but subsequently showed very poor response to antidepressant therapy. Her presentation gradually and dramatically progressed into full blown dementia within couple of years. Brain MRI showed atrophic cortical changes and subcortical white matter alterations consistent with Alzheimer’s dementia. Brain PET scan revealed reduction in cerebral glucose metabolism in temporoparietal areas bilaterally most consistent with Alzheimer’s dementia. There was a strong family history of early-onset dementia. A final diagnosis of young onset dementia was made, and unfortunately, she passed away at the age of 44 years.